Study of liver function tests in hypertensive disorders of pregnancy - Pusuloori, Radhika; Arora, K. Dilzith (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders of pregnancy with spectrum complications is one among leading causes of feto-maternal morbidity and mortality especially when its associated with HELLP syndrome. Methods: The present prospective study was conducted over a period of three years in the department of obstetrics and gynecology at Chalmeda Anandarao Institute of Medical Sciences, Karimnagar, Telangana from January 2008 to January 2009. This is a prospective study on 50 pregnant women with 28-40 weeks of gestation with diastolic BP ≥110 mm Hg recorded 6 hours apart. Results: This is a prospective study on 50 pregnant women with 28-40 weeks of gestation with diastolic BP≥110 mm Hg recorded 6 hours apart. Severe pre eclampsia was seen in younger age group ˂25 years. In patients with raised LFTs unbooked cases were more (64%) showing complications are more in unbooked cases. Renal complications are seen in 16% of the total cases and in 28% of the cases with raised LFTs. In overall study group number of primi gravid were 50% and multi were 27%. Incidence of severe pre eclampsia was 78% in overall cases. In patients with raised LFTs the incidence was 30 (88%). Conclusions: Detection of increased LFTs in cases of severe pre-eclampsia is a risk category, associated with increased rate of feto-maternal complications, compared to severe pre-eclampsia with normal LFTs. Such cases need special attention with early detection and referral to higher centre with better facilities of NICU set up to reduce the complications and mortality.